2023
DOI: 10.51866/oa.232
|View full text |Cite
|
Sign up to set email alerts
|

Chronic musculoskeletal pain among elderly individuals in a rural area of West Bengal: A mixed-method study

Abstract: Introduction: The high prevalence among elderly individuals and potential adverse impact on their overall life quality make chronic musculoskeletal pain a significant public health concern. Chronic musculoskeletal pain is an important cause of self-medication, which must be addressed to avoid various side effects and improve elderly health. This study aimed to determine the prevalence of chronic musculoskeletal pain and its associated factors among individuals (age ≥60 years) in rural West Bengal and explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…I read with interest the article by Sengupta et al on a mixed-method study of 255 elderly patients with musculoskeletal pain (MSP) evaluated using a structured questionnaire. 1 The study showed that 57% of the enrolled patients reported MSP, with the knee joint being the most commonly affected site. Multivariate analysis revealed that comorbidity, age, depression and drug use were associated with MSP It was concluded that the treatment of MSP should focus on managing comorbidities, providing mental support and informing about the side effects of over-the-counter analgesics.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…I read with interest the article by Sengupta et al on a mixed-method study of 255 elderly patients with musculoskeletal pain (MSP) evaluated using a structured questionnaire. 1 The study showed that 57% of the enrolled patients reported MSP, with the knee joint being the most commonly affected site. Multivariate analysis revealed that comorbidity, age, depression and drug use were associated with MSP It was concluded that the treatment of MSP should focus on managing comorbidities, providing mental support and informing about the side effects of over-the-counter analgesics.…”
mentioning
confidence: 96%
“…Another limitation of the study is that MSP was not defined. 1 It is crucial to determine whether the authors meant pain due to an orthopaedic, a neurological or a rheumatological problem. The definition of chronic MSP was also unclear.…”
mentioning
confidence: 99%
“…Notably, the objectives of our study were to assess the burden of chronic musculoskeletal pain (MSP) among the elderly population and delineate patients’ perspectives towards the treatment and management of MSP using a mixed-method approach. 2 The qualitative component of the study was conducted to determine how elderly patients experiencing chronic MSP feel and think about the treatment available to them and how they approach their pain management.…”
mentioning
confidence: 99%
“…Exercises have been shown to have several positive effects, such as pain reduction 9 , improved quality of life 10 and well-being 11 . People in rural regions are equally affected but have limited access to adequate treatment 12,13 .One way to offer exercises for the treatment of MSD is via a mobile application that showed positive results regarding pain reduction and improved quality of life in neck pain 14,15 and LBP 16,17 . Mobile applications can provide access to appropriate exercise for a large number of people, especially in rural areas [18][19][20] .…”
mentioning
confidence: 99%